Proceedings of the 2nd ACM TRECVid Video Summarization Workshop 2008
DOI: 10.1145/1463563.1463568
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the utility of fast-forward surrogates for bbc rushes

Abstract: This paper discusses in detail our approaches for producing the video summaries submitted to the TRECVID 2008 BBC rushes summarization task, including the baseline method. Empirical work produced during and after the TRECVID 2007 rushes summarization task gave strong evidence that a simple 50x method (sampling every 50 th frame) provides excellent coverage (text inclusion performance). Our submissions for TRECVID 2008 investigated the effects of junk frame removal, including a comprehensible audio track, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…For example, the fast-forward surrogate of playing a BBC rushes source video at 50× to produce a 2% summary leverages no context aside from the removal of "junk" frames (color bars, scene clappers) [92]. Multimedia surrogates representing a single multimedia document or sets of documents also can be improved through interactive user control and user context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the fast-forward surrogate of playing a BBC rushes source video at 50× to produce a 2% summary leverages no context aside from the removal of "junk" frames (color bars, scene clappers) [92]. Multimedia surrogates representing a single multimedia document or sets of documents also can be improved through interactive user control and user context.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment found that the skim was more effective if composed of longer 5-second phrasealigned audio chunks than shorter 2.5-second chunks [1]. For BBC rush materials with much redundancy due to repeated takes, 50× worked nearly as well as 25× and offered much greater efficiency [91], with the contribution of an audio component to the playable 50× summary still an open area of investigation [92]. Playable video summaries have received renewed attention from the TRECVID community in its BBC Rushes Summarization Task, looking at indicative and informative summaries that have at most 4% of the source length in 2007, and 2% of the source length in 2008.…”
Section: H a P T E Rmentioning
confidence: 99%
“…They match and mosaick the extracted key frames to reduce content redundancy and to build compact visual summaries. Christel et al [276] have constructed a baseline rushes summarization system at TRECVid 2008 [272]. This baseline method simply presents the entire video at 50×normal speed.…”
Section: A Key Frame-based Static Abstractsmentioning
confidence: 99%
“…The baseline simply presented the entire video at 50× normal speed -a strategy arrived at after study of various alternatives [6]. The baseline was mute with no audio whatsoever.…”
Section: Participants and Their Approachesmentioning
confidence: 99%